China, ¿aliado o adversario? Un análisis de los impactos económicos del gigante asiático en Latinoamérica durante el periodo 1990-2014 - Aviles Quintanar, Diego Alberto (Posgrados de la División de Ciencias Económica Administrativas, 2022)
The size of the Chinese market, as well as the speed of its growth, its openness to the outside world and its commercial performance, have been felt in LatinAmerica in different ways. China and its dynamism with the international economy have had different impacts in the Latin American region. In the article you will find reflections on China and its global expansion in the economy, and the question of whether that nation has been an ally or an adversary.Both positions or behaviors are defined for Latin American countries, depending on the country analyzed.